The role of trust in the primary adoption stage of management accounting innovations - Robalo, Rui (2017)
A narrative inquiry grounded in interpersonal trust is advanced to examine the primary adoption stage of management accounting innovations in a Portuguese public sector organisation, where the adoption processes were promoted by management accountants. We studied the ways in which management accountants (trustees) built up trust in themselves in relation to the adoption of management accounting innovations (object of trust) with the intention of convincing top-level managers (trustors) to authorise their adoption. We gathered evidence to show that, through time, management accountants built up increasing levels of contractual trust, competence trust, and goodwill trust as a means of convincing top-level managers, to authorize the adoption of management accounting innovations.